PERAN PENDIDIDKAN BAGI KEHIDUPAN MANUSIA DALAM PANDANGAN AL-QURAN - Fahmi Sahlan; Nabil Nabil; Dariyanto Dariyanto (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACTThe process of cultural growth is triggered by education. Education is the key to all progress of human life throughout history. In the beginning, education developed from simple (primitive) with survival characteristics, surviving from the threats of the surrounding environment. From here humans develop the skills of the tools to find and produce the necessities of life and maintain them. Education here is not only for skills development but for the development of theoretical and practical abilities based on scientific thinking concepts.This study aims to determine the role of education for human life in the view of the Koran and its implementation related to the media of the verses of the Koran and its interpretation of the role of education.The results of the study show that education is an important issue for all people. Education has always been the cornerstone of hope for developing individuals and society. Education also functions as a tool to advance civilization, develop society and enable generations to do much for their interests. Therefore, the role of education according to the view of the Koran is as a means of transforming science and technology and especially as a means of internalizing the noble values of religious teachings and national culture in accordance with religious law. Keywords: The Role of Education, Human Life, Ayat-ayat Al-Quran